Volatility linkages between agricultural commodity prices, oil prices and real USD exchange rate: The case of Colombia; Vínculos de volatilidad entre precios de productos agrícolas, precios del petróleo y tipo de cambio del dólar estadounidense - Mohammed Seghir Guellil; Mostéfa Belmokaddem; Mohamed Benbouziane (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
This study examines the dynamic nexus betwixt oil prices, twenty-two world agricultural commodity prices and given the evolution of the relative strength of the US dollar in a panel setting. We use panel cointegration and Panel Granger causality methods for a panel of twenty-two agricultural products based on annual observations ranging from 1980 to 2015. The empirical results provide a strong evidence of long-term relationship between Agricultural Commodity Prices, Oil Prices and Real USD Exchange Rate. Contrary to the findings of many studies in the literature that report neutrality of agricultural prices to oil price changes, we find strong support of bi-directional causal linkages among Agricultural Commodity Prices, Oil Prices and Real USD Exchange Rate. The long-run causality analysis thereby implies that the oil prices and the dollar have a predictive power to forecast the agricultural prices, which could be a good tool to prioritize the allocation of resources across industries to ensure agricultural scenario in general and economic outcomes.
Keywords: B22; C33; C51; F31; N50; Q02; Q11; Q41; 330; Oil prices; exchange rates; agricultural commodity prices; panel cointegration